Influence of Y/Zn Ratio on Secondary Phase Strengthening of Mg-Y-Zn Alloy - Jie Hu; Jiageng Wu; Xiangquan Liu; Dong Zhao; Liang Liang; Jian Peng (Metals)
By adjusting the Y/Zn (wt.%) ratio while maintaining the total mass of Y and Zn unchanged, the evolution of the microstructure and mechanical properties of Mg-Y-Zn alloy castings with different phase types was investigated. The results indicated that the studied alloy exhibited a typical <semantics>α</semantics>-Mg dendritic structure, which contained intermetallic compounds such as phase I, phase I + W, phase W + LPSO, and phase LPSO. The phase evolution process of Mg-Y-Zn alloys was analyzed in conjunction with microstructural observations. The strengthening effects on the mechanical properties of five alloys with different compositions revealed that as the Y/Zn ratio increased, secondary phase strengthening gradually became the primary strengthening mechanism, with the contribution order being W + LPSO > LPSO > I + W > I.